Lloyd Kim. Polemic in the Book of Hebrews: Anti-Judaism, Anti-Semitism, or Supersessionism? Princeton Theological Monograph Series 64 - Massena, Andrew (Studies in Christian-Jewish Relations, 2013)
No abstract is available.